Faith communities, youth and development in Mozambique - Chifeche, Victoria; Dreyer, Yolanda (HTS Teologiese Studies / Theological Studies, 2019)
In Mozambique, poverty is pervasive because of factors such as the civil war (1976–1992) and its aftermath, political instability, food scarcity and natural disasters. This article elucidates the situation of post-civil war Mozambique from a socio-political perspective with a specific focus on children and the youth as a particularly vulnerable group. Many children and young people have been displaced and are subject to work exploitation and sexual abuse. Female children also fall victim to the cultural practice of child marriage. The absence of comprehensive social measures for the protection of vulnerable young persons has a detrimental effect on their welfare and future prospects. The aim of the article is to explore the role that faith communities and church institutions can play in this context. From an inclusive congregational perspective, the inclusion of youth in all aspects of faith communities as a strategy for development is discussed. From a human rights and theological perspective, participatory action is required for faith communities and church institutions to contribute to making a life of human dignity possible for children and young people.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; institutions / instituições; youth / juventude

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Conferência Internacional Sobre a Educação da Rapariga - ROSC (ROSC - Fórum da Sociedade Civil para os Direitos da Criança, 2019)
O Movimento de Educação para Todos (MEPT) em coordenação com o Ministério da Educação e Desenvolvimento Humano (MINEDH), realizou nos dias 6 e 7 de Junho do corrente ano, em Maputo, a Conferência Internacional Sobre a Educação da Rapariga com o lema “Desafios, Partilha de Experiências e Boas Práticas para Assegurar a Retenção da Rapariga no Sistema de Ensino.” Esta conferência tinha como objetivos: → Troca de experiências em torno de políticas e práticas existentes a nível nacional e internacional para assegurar a retenção da rapariga no sistema de ensino e discutir estratégias e possíveis soluções para a redução dos índices de abandono escolar por parte das raparigas na África Subsariana; → Apreciar os instrumentos e experiências existentes para prevenir a gravidez infantil e combater a violência baseada no género nas escolas a nível da região; → Olhar para os instrumentos e experiências existentes de boas práticas na região para o tratamento de casos de alunas grávidas nas escolas e a sua reintegração.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (RIA Policy Paper, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde